Melihat Tata Krama dari Kacamata Islam (Analisa Ayat-Ayat Al-Qur’an) - Abd. Aziz (HUMANISTIKA : Jurnal Keislaman, 2017)
A true Muslim applies the commandments of the Qur’an and Sunnah in his daily life. A true Muslim is not he who chooses from Islam what suits him and then leaves the other pa besides him. As a religion Islam provides a framework that shapes the moral and ethical behavior of Muslims around the world. The Qur’an is very clear about the importance of high morality by saying to the Prophet “Wainnaka laala khuluqin Adzeem” which means “And indeed, you have an extraordinary moral character”. And say “You and you certainly have the most noble standard of moral excellence”. Fortunately, in Islam the question of whether an act is regarded as a virtue or a conflict is determined in the Qur’an and Sunnah, then the meaning of the sunnah is “the words of the Prophet, which largely derive from his words and actions.